MIS-C Treatment: Is IVIG Always Necessary? - Licciardi, Francesco; Baldini, Letizia; Dellepiane, Marta; Covizzi, Carlotta; Mogni, Roberta; Pruccoli, Giulia; Orsi, Cecilia; Rabbone, Ivana; Parodi, Emilia; Mignone, Federica; Montin, Davide (Frontiers in Pediatrics, 2021)
Background: MIS-C is a potentially severe inflammatory syndrome associated with SARS-CoV-2 exposure. Intravenous immunoglobulin (IVIG) is considered the first-tier therapy, but it implies infusion of large fluid volumes that may worsen cardiac function. Patients and Methods: Since April 2020, we have developed a treatment protocol that avoids the infusion of IVIG as first-line therapy in the early phase of MIS-C. In this study, we retrospectively analyzed a cohort of consecutive patients treated according to this protocol between 01/04/2020 and 01/04/2021. Results: In the last year, 31 patients have been treated according to the protocol: 25 with high-dose pulse MP (10 mg/kg) and 6 with 2 mg/kg. 67.7% of the patients responded to the initial treatment, while the others needed a step-up, either with Anakinra (25.8%) or with MP dose increase (6.5%). IVIG was administered in four patients. Overall, only one patient (3.2%) needed ICU admission and inotropic support; one patient developed a small coronary artery aneurysm. Conclusions: Timely start of MP therapy and careful fluid management might improve the outcomes of MIS-C patients.